2021
DOI: 10.3390/su13031410
|View full text |Cite
|
Sign up to set email alerts
|

Use of Decision Trees to Evaluate the Impact of a Holistic Music Educational Approach on Children with Special Needs

Abstract: In this study, decision trees were used to develop a pre-assessment model to help ascertain the impact of music education on children with special needs. The focus of the study was the application of an educational curriculum for 16 weeks, five sessions of 40 min duration per week, using the Holistic Music Educational Approach for Young Children (HMEAYC). The pilot program was implemented with children with special needs to measure its learning effectiveness. The methodology proved a better indicator for impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Data from this study confirm that the HMEAYC showed a significant improvement in indicator values, such as language expressiveness, language comprehension, physical movement, social skills, interpersonal relationships, self-directedness, and autonomy for children with developmental delay. The result was consistent with past studies [ 18 , 19 , 20 , 21 , 22 , 28 , 29 , 30 ]. This study supports past studies on implementing the HMEEAYC curriculum for young children with developmental delay in Taiwan.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Data from this study confirm that the HMEAYC showed a significant improvement in indicator values, such as language expressiveness, language comprehension, physical movement, social skills, interpersonal relationships, self-directedness, and autonomy for children with developmental delay. The result was consistent with past studies [ 18 , 19 , 20 , 21 , 22 , 28 , 29 , 30 ]. This study supports past studies on implementing the HMEEAYC curriculum for young children with developmental delay in Taiwan.…”
Section: Discussionsupporting
confidence: 94%
“…When the dependent variable is the categorical form, the decision tree is established as a classification tree. In this study, the classification and regression trees (CART) [ 21 , 31 ] apply the Gini index as the criterion for determining branching variables and classifying the data in each branch node to establish a structure of the decision tree with binary classification.…”
Section: Data and Empirical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pursuit of quality and efficiency of education has been the focus of much educational research [1][2][3]. It has become a crucial issue for many educational experts and scholars to study how to improve educational methods to improve the quality of education and meet the needs of students [4][5][6][7]. Scholars [4] believed that current educational styles would be very unpredictable if massive defects existed in educational methods and knowledge.…”
Section: Introductionmentioning
confidence: 99%